A feasibility study of a novel low-level light therapy for digital ulcers in systemic sclerosis. (3rd April 2019) - Hughes, M.; Moore, T.; Manning, J.; Wilkinson, J.; Watson, S.; Samraj, P.; Dinsdale, G.; Roberts, C.; Rhodes, L. E.; Herrick, A. L.; Murray, A.
Abstract: Background: Locally acting, well-tolerated treatments for systemic sclerosis (SSc) digital ulcers (DUs) are needed. Objectives: Our primary aim was to investigate the safety, feasibility, and tolerability of a novel low-level light therapy (LTTT). A secondary aim was to tentatively assess efficacy. Methods: A custom-built device comprising infrared (850 nm), red (660 nm), and violet (405 nm) LEDs was utilized. DUs were irradiated with 10 J/cm 2 twice weekly for 3 weeks, with follow-up at weeks 4 and 8. Any safety concerns were documented. Patient opinion on time to deliver, feasibility, and pain visual analogue score (VAS; 0–100, 100 most severe) was collected. Patient and clinician DU global assessment VAS were documented. DUs were evaluated by laser Doppler perfusion imaging pre- and post-irradiation. Results: In all, 14 DUs in eight patients received a total of 46 light exposures, with no safety concerns. All patients considered LTTT 'took just the right amount of time' and was 'feasible', with a low associated mean pain VAS of 1.6 (SD: 5.2). Patient and clinician global DC VAS improved during the study (mean change: –7.1 and –5.2, respectively, both p  < .001). DU perfusion significantly increased post-irradiation. Conclusions: LTTT for DUs is safe, feasible, and well tolerated. There was an early tentative suggestion of treatment efficacy.